Level of episiotomy practice and its disparity among primiparous and multiparous women in Ethiopia: a systematic review and meta-analysis - Fantu Mamo Aragaw; Daniel Gashaneh Belay; Daniel Gashaneh Belay; Mastewal Endalew; Melaku Hunie Asratie; Moges Gashaw; Nuhamin Tesfa Tsega (Frontiers Media S.A., 2023)
BackgroundEpisiotomy at the time of vaginal birth is a common lifesaving surgical procedure. In Ethiopia, several studies have been conducted concerning the proportion of episiotomy. However, its prevalence varies across these series of studies. Thus, this systematic review and meta-analysis aimed to estimate the level of episiotomy practice and its disparity among primiparous and multiparous women in Ethiopia.MethodsThis systematic review was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline. We systematically searched the PubMed/MEDLINE, EMBASE, Google Scholar, and Science Direct databases for studies conducted in Ethiopia focusing on episiotomy. We included all cross-sectional studies published until October 5,2022. Data were analyzed using R version 4.2.1 software. The pooled estimates with 95% confidence intervals (CIs) were presented using forest plots. A random-effects meta-analysis was conducted on extracted crude rates to calculate the national and regional pooled estimates for the country. The I-squared test and Egger's regression test were used to assess heterogeneity and publication bias, respectively.ResultsOur search yielded 390 articles. A total of 13 studies covering five administrative regions and 6,404 women who delivered vaginally were involved. The mean age of the study participants ranged from 22 to 27.7 years. The estimated overall pooled prevalence rate of episiotomy in Ethiopian women was 42.75% (95% CI: 34.97%-50.54%). In the subgroup analysis, the pooled prevalence rate of episiotomy was 61.45% (95% CI: 51.11%-71.80%) among primiparous women. Meanwhile, the pooled estimate appears to be approximately 30.47% (95% CI: 22.08%-38.85%) among multiparous women.ConclusionOur findings concluded that the pooled prevalence rate of episiotomy was higher than the evidence-based WHO recommendations for optimal patient care. Parallel to this, nulliparous women had a higher episiotomy rate than multiparous women. These findings highlight the importance of continued training for labor ward staff, particularly healthcare providers who often perform the majority of deliveries.